Hingehoid Eesti vaimulike pilgu läbi - Ivanova, Maire; Lehtsaar, Tõnu (Usuteaduslik Ajakiri, 2009)
Pastoral Care through the Eyes of Estonian Clergy This article focuses on the results of four focus group interviews with the pastors of four main Protestant denominations in Estonia: Estonian Evangelical Lutheran Church, Estonian Federation of Evangelical Baptist Congregations, Estonian Christian Pentecostal Church and Estonian Methodist Church. The goal of the survey was to investigate the types of pastoral care in Estonian Protestant denominations and to find out whether the church been able to adapt its work to meet the people’s needs. The two main topics of pastoral counselling are conflicts and the question of suffering. Pastoral care can work on different levels, starting from general Christian friendship and ending with personal pastoral counselling or spiritual direction. The church is an already-existing social network where many pastoral issues can be solved or even prevented without reaching out for psychological help, since pastoral care is a combination between psychological and theological knowledge and relationship with God. Trusting atmosphere and confidentiality are the key factors in creating a safe environment for pastoral care. Lay members can reach far more people than the clergy and therefore their activities in pastoral care cause both quantitative and qualitative church growth. The outcome of this survey establishes the following the key issues: a) the training of the pastoral caregivers and b) the general vision of the church: how to develop the pastoral care according to the needs of the society.